2017
DOI: 10.5493/wjem.v7.i2.42
|View full text |Cite
|
Sign up to set email alerts
|

Recent clinical trials of cancer immunogene therapy in companion animals

Abstract: This mini-review presents the results of veterinary clinical trials on immunogene therapy published from 2014 to 2016. A variety of tumors, among them melanoma (canine and equine), mastocytoma (canine), mammary adenocarcinoma (canine) and fibrosarcoma (feline) were treated by using diverse strategies. Non-viral vectors were usually employed to transfer genes of cytokines, suicide enzymes and/or tumor associated antigens. In general terms, minor or no adverse collateral effects were related to these procedures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…These types of vaccine platforms have mostly been applied to protozoal and helminth parasites of medical and veterinary importance with some promising evidence for use in ticks (Ghosh et al, 2007 ; Guerrero et al, 2014 ; Wedrychowicz, 2015 ; Qian et al, 2016 ; Tebeje et al, 2016 ; Noon and Aroian, 2017 ). Currently, only a single plasmid vector has been approved for human DNA vaccine design (Halstead and Thomas, 2011 ), and a limited number of DNA vaccines have been commercialized against viral pathogens and cancer treatment (e.g., Oncept®, Merial Inc.) in animals (Wahren and Liu, 2014 ; Finocchiaro and Glikin, 2017 ). For metazoan parasite vaccines, however, these types of vaccine strategies appear only to be used for initial antigen screening purposes (e.g., expression library immunization) or as pre-clinical evaluations (as either sole or prime-boost strategies) in spite of the availability of newer technologies (e.g., minimized non-viral vectors) (Hardee et al, 2017 ).…”
Section: Metazoan Vaccine Development: Identification To Formulationmentioning
confidence: 99%
“…These types of vaccine platforms have mostly been applied to protozoal and helminth parasites of medical and veterinary importance with some promising evidence for use in ticks (Ghosh et al, 2007 ; Guerrero et al, 2014 ; Wedrychowicz, 2015 ; Qian et al, 2016 ; Tebeje et al, 2016 ; Noon and Aroian, 2017 ). Currently, only a single plasmid vector has been approved for human DNA vaccine design (Halstead and Thomas, 2011 ), and a limited number of DNA vaccines have been commercialized against viral pathogens and cancer treatment (e.g., Oncept®, Merial Inc.) in animals (Wahren and Liu, 2014 ; Finocchiaro and Glikin, 2017 ). For metazoan parasite vaccines, however, these types of vaccine strategies appear only to be used for initial antigen screening purposes (e.g., expression library immunization) or as pre-clinical evaluations (as either sole or prime-boost strategies) in spite of the availability of newer technologies (e.g., minimized non-viral vectors) (Hardee et al, 2017 ).…”
Section: Metazoan Vaccine Development: Identification To Formulationmentioning
confidence: 99%
“…Therefore, in the veterinary oncology context, the development of new simple and affordable approaches is compelling. Along this way, cancer immunogene therapy is an especially suitable and fast expanding field that was reasonably explored for malignant melanoma and other kinds of canine spontaneous tumors [ 9 , 10 ]. It is worth mentioning that three small trials of immunogene therapy for mammary carcinoma have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Some types of human cancer are very similar to the corresponding disease in companion animals. The auspicious results, derived from immunogene therapy studies carried out in companion animals, warrant their usage in veterinary clinical oncology [ 1 , 2 ]. Progress made with veterinary cancer bearing patients can significantly speed up translational research and benefit both veterinary and human patients.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant melanoma (MM) is rare in cats while is one of the most common tumors in dogs [ 1 - 6 ]. Being clinically similar, both diseases are chemo and radioresistant and share similar phenotypes [ 3 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation